“Cerebellar Challenge” for Older Adults: Evaluation of a Home-Based Internet Intervention - Gallant, Zoe; Nicolson, Roderick I. (Frontiers in Aging Neuroscience, 2017)
There is converging evidence that maintenance of function in the multiple connectivity networks involving the cerebellum is a key requirement for healthy ageing. The present study evaluated the effectiveness of a home-based, internet-administered ‘cerebellar challenge’ intervention designed to create progressive challenges to vestibular function, multi-tasking, and dynamic coordination. Participants (n=98, mean age 68.2, sd 6.6) were randomly allocated to either intervention (the cerebellar challenge training for 10 weeks) or no intervention. All participants undertook an initial series of pre-tests, and then an identical set of post-tests following the intervention period. The test battery comprised five suites of tests designed to evaluate cognitive-sensori-motor-affective functions, including Physical Coordination, Memory, Language Dexterity, Fluid Thinking and Affect. The intervention group showed significant pre- to post improvements in 9 of the 18 tests, whereas the controls improved significantly on one only. Furthermore, the intervention group showed significantly greater improvement than the controls on the ‘Physical Coordination’ suite of tests, with evidence also of differential improvement on the Delayed Picture Recall test. Frequency of intervention use correlated significantly with the improvement in balance and in peg-moving speed. It is concluded that an internet-based cerebellar challenge programme for older adults can lead to benefits in balance, coordination and declarative memory. Limitations and directions for further research are outlined.